Migrant and Refugee Impact on Well-Being in Rural Areas: Reframing Rural Development Challenges in Greece - Papadopoulos, Apostolos G.; Fratsea, Loukia-Maria (Frontiers in Sociology, 2021)
The paper aims to exemplify and discuss the changing conditions and challenges posed by the newly arriving populations of migrants and refugees in rural Greece, along with local people’s views on the impact of the new arrivals in their rural places. Its main objective is to understand whether migrants and refugees create threats or opportunities for the local population, and whether movers and non-movers have a shared understanding of well-being in their rural areas. The analysis unveils the connections that are emerging between migrants and refugees and the economy, society and culture in rural receiving areas. Thus, the paper aims at showing the complexity of rural migrant flows and how the interactions between migrants, refugees and locals in the light of the well-being of rural areas may inform rural development in Greece. The paper is structured into five main sections following the introduction. The first section contains a discussion of the main concepts used as building blocks for creating a theoretical framing of well-being in rural areas. The second section develops a brief discussion of international and internal migration to rural areas in Greece, as well as providing some contextual information on the impact of the economic crisis and new developments in response to the recession. The third section includes a short presentation of the methodological approach and a description of the case study area. The fourth section is dedicated to an analysis of the narratives of international migrants, refugees, internal migrants, locals and stakeholders. Finally, the concluding section critically discusses the conceptualisations of rurality and well-being between the various population groups and articulates the challenges connected to well-being and mobilities in contemporary rural Greece.